The Use of Traditional Health Services and Their Determinants in The Coastal Area of Laha Village of Ambon City, Indonesia - Maxwell Landri Vers Malakauseya; Johan Bruiyf Bension; Marten Yoseph Matakupan; Sean Semuel Istia; Christiana Rialine Titaley; Hotmaida Yumni Ajrina; Fadila Tri Starlia; Noviyanter Siahaya; Etrin Zulqarnain Eka Saputra Linggar; Augie Desvie Klausya Kadun (Future Science, 2023)
Traditional health services are one of the alternative treatments used by the community in Indonesia. Some even preferred using traditional health services as the primary treatment than modern health services. This study analyzed factors associated with using traditional health services in the coastal area of Laha Village, Ambon City. Data were derived from a household health survey conducted in the coastal area of Laha Village in November 2022. The dependent variable was the use of traditional health services. Independent variables included demographic status, lifestyle, and the history of illness. This analysis employed multivariate logistic regression methods to analyze factors associated with using traditional health services. We found an increased odds of using traditional health services in respondents aged >60 years (aOR=4.13; 95%CI: 1.47-11.55; p=0.007), who owned a family medicinal plants (aOR=25.18; 95%CI: 12.41-51.07 p<0.001), and who never smoked cigarettes (aOR=3.45; 95%CI: 1.31-9.05; p=0.012). This study also examined the association between the history of illness respondents had and the use of traditional health services. We found a significant association between the history of joint diseases (aOR=2.34; 95%CI: 1.37-4.02; p=0.002) and injury (aOR=0.30; 95%CI: 0.16-0.56; p<0.001) with the use of traditional health services. This study shows the need for health promotion efforts on the utilization of traditional health services in the community to increase knowledge and correct understanding regarding the utilization of traditional health services.